Can Artificial Intelligence Be the Key to Reducing Hospital Readmissions? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Can Artificial Intelligence Be the Key to Reducing Hospital Readmissions? Keywords: AI in healthcare, hospital readmissions, machine learning, predictiv...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Patient Care; Machine Learning